Global Health Innovation: Reaching New Heights in Nepal - Sarala Adhikari; Sakar Subedi; William Neville Grut; Andrew John Macnab (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
The role of charities and other non-governmental organizations is to address social, humanitarian, and environmental issues by providing services, advocating for change and mobilizing communities. The purpose of Rose Charities Canada is to help people around the world to overcome poverty through education, community support and healthcare. Listening to communities and collaborating with them to find solutions to the problems they identify is the core process, and this requires strong leadership, the dedication of local staff and industrious volunteers. Innovative projects and partnerships in healthcare, education and community support are central to the mission of effective charities. The value of international meetings in this context is that ‘what works and why’ can be shared and the lessons learned translated to benefit other communities. A recent international meeting in Kathmandu highlighted how Nepal is taking global health innovation to new heights.